Effectiveness of a breastfeeding self-efficacy intervention on BSES-SF scores and exclusive breastfeeding: a quasi-experimental study in postpartum mothers - Arifarahmi Arifarahmi; Asrial Asrial; Muhammad Rusdi; Solha Elrifda (International Journal of Public Health Science (IJPHS), 2026)
Despite Indonesia's national breastfeeding promotion efforts, exclusive breastfeeding rates remain below the 80% target, with limited evidence on structured breastfeeding self-efficacy (BSE) interventions in low-resource Indonesian settings. To evaluate the effectiveness of a BSE intervention on BSES-SF scores and exclusive breastfeeding continuation during the first six months postpartum. A quasi-experimental pretest-posttest design with a control group was conducted on 104 postpartum mothers (52 intervention, 52 control). Measurements were conducted longitudinally at baseline, weeks 2, 6, 12, and 24 postpartum. Data were analyzed using independent t-test, Chi-square, Cox proportional hazard regression, and linear mixed model (LMM). The intervention group's BSES-SF score increased significantly from 42.35 to 59.73 compared to the control group (41.88 to 48.06, p < 0.001). Exclusive breastfeeding at 24 weeks was significantly higher in the intervention group (71.2% vs. 40.4%, RR = 1.76, p = 0.001). Cox analysis identified the intervention as the strongest protective factor (HR = 0.41, p = 0.001), followed by husband's support (HR = 0.54, p = 0.039), while employment was a risk factor (HR = 1.72, p = 0.034). The non-randomized design and single-site setting may limit generalizability. The BSE intervention effectively increased self-efficacy scores and exclusive breastfeeding rates, suggesting integration into routine postpartum care as a scalable public health strategy.